Atrial fibrillation and the risk of cardiovascular disease and mortality in the Hypertension in the Very Elderly Trial. Issue 5 (May 2020) - Antikainen, Riitta L.; Peters, Ruth; Beckett, Nigel S.; Rajkumar, Chakravarthi; Bulpitt, Christopher J.
Abstract : Objective: To assess the prognostic value of electrocardiographic atrial fibrillation in older hypertensive people in the randomized, placebo-controlled Hypertension in the Very Elderly Trial. Methods: Hypertension in the Very Elderly Trial randomized 3845 hypertensive people aged 80 years and over, 3273 with electrographic data on the presence or absence of atrial fibrillation at baseline and without established cardiovascular disease. Multivariate Cox proportional hazard models were used to estimate hazard ratios with 95% confidence intervals (CIs) for all-cause mortality, incident fatal and nonfatal major cardiovascular events, all-stroke and all-heart failure. The mean follow-up time was 2.1 years. Results: Baseline prevalence of atrial fibrillation was 5.8%. Compared with people without atrial fibrillation at baseline, after adjustments the presence of atrial fibrillation was associated with increased risk of mortality (hazard ratio = 2.49, 95% CI = 1.80–3.44, P  < 0.001), of nonfatal and fatal cardiovascular events (hazard ratio = 2.47, 95% CI = 1.71–3.55, P  < 0.001), all-stroke (hazard ratio = 2.47, 95% CI = 1.34–4.56, P  = 0.004) and all-heart failure (hazard ratio 2.33, 95% CI = 1.10–4.93, P  = 0.027). Conclusion: Atrial fibrillation is an important risk factor to consider when assessing older hypertensive adults as it is associated with increased risk of mortality, nonfatal and fatal cardiovascular events, stroke and heart failure.